2006
DOI: 10.1016/j.aquaculture.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross effects of the strain of dietary Saccharomyces cerevisiae and rearing conditions on the onset of intestinal microbiota and digestive enzymes in rainbow trout, Onchorhynchus mykiss, fry

Abstract: Two strains of Saccharomyces cerevisiae were tested as probiotics for rainbow trout fry, during the first month of feeding. Each strain was introduced into separate diets, at the rate of 106 CFU g− 1 and their effects were compared with those of a control diet. Two rearing conditions were simultaneously compared, to test the adaptability of the probiotic treatment. From start feeding onwards, the water supply came from either spring or river, resulting in two different temperature ranges, 11-11.5 and 7-8 °C re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 27 publications
8
83
1
4
Order By: Relevance
“…Similar benefits have been reported in fish fed dietary glucan (Masahiro, 1999, Meena et al, 2012, Soltanian et al, 2009. Growth rate possibly enhanced due to the energetic benefits obtained through glucan (Ai et al, 2007), microbial manipulation of intestinal microbiota (Ringø et al, 2010), colonization of lactic acid bacteria (as seen in our results; Table 3) in the gut and production of protease and amylase by these bacteria in the digestive tract (Farzanfar, 2006, Gullian et al, 2004, Irianto and Austin, 2002, Waché et al, 2006, Hoseinifar et al, 2011a. In addition, enumeration of LAB increases the concentrations of the volatile fatty acids (VFA s ) which beneficially affect microvillus morphology and nutrient utilization (Daniels et al, 2010, Dimitroglou et al, 2009, Ringø et al, 2010, Salze et al, 2008, Zhou et al, 2010.…”
Section: Discussionsupporting
confidence: 73%
“…Similar benefits have been reported in fish fed dietary glucan (Masahiro, 1999, Meena et al, 2012, Soltanian et al, 2009. Growth rate possibly enhanced due to the energetic benefits obtained through glucan (Ai et al, 2007), microbial manipulation of intestinal microbiota (Ringø et al, 2010), colonization of lactic acid bacteria (as seen in our results; Table 3) in the gut and production of protease and amylase by these bacteria in the digestive tract (Farzanfar, 2006, Gullian et al, 2004, Irianto and Austin, 2002, Waché et al, 2006, Hoseinifar et al, 2011a. In addition, enumeration of LAB increases the concentrations of the volatile fatty acids (VFA s ) which beneficially affect microvillus morphology and nutrient utilization (Daniels et al, 2010, Dimitroglou et al, 2009, Ringø et al, 2010, Salze et al, 2008, Zhou et al, 2010.…”
Section: Discussionsupporting
confidence: 73%
“…These analyses showed significant differences in the fungal profiles between the two groups of alevins after the first 5 days of feeding. A previous study with culturedependent methods pointed out the importance of early colonisation by yeast in the gut of rainbow trout for the maturation of the digestive system (Waché et al, 2006). In human gut microbiome, the increased abundance of Candida due to high-carbohydrate diets was related to its contribution to starch digestion (Hoffmann et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…However, for the first time is reported its use in diets with high contents of soybean meal. The improved growth of juveniles fed the Diets Y and Y+Ph might be related to a better nutrient digestibility, particularly the protein fraction (Lara-Flores et al, 2003;Waché et al, 2006) and the results of the present research indicates that yeast might contribute to this. During the feeding trials we were not able to determine the protein digestibility, but Bureau et al (2002) reported that N excretion and oxygen consumption might be useful to estimate the nutrient utilization of diet, as usually, low values indicates a better use of the protein (less N excretion) and less energy spent in its oxidation (less oxygen consumption).…”
Section: Discussionmentioning
confidence: 69%